EFFECT OF FORENSIC ACCOUNTING ON THE PERFORMANCE OF DEPOSIT MONEY BANKS IN NIGERIA - Garba , ADAMU (The journal of contemporary issues in business and government, 2024)
This study investigated the effect of forensic accounting on the performance of Deposit Money Banks (DMBs) in Nigeria, focusing on the period from 2019 to 2023. A sample of 12 DMBs was analyzed using panel data analysis, employing both fixed and random effect regression models. The Hausman test indicated a p-value of 0.5876, signifying that the random effect model is the most appropriate for this analysis. The study specifically examines the impact of three forensic accounting components: Risk Assessment (RAS), Legal Services (LES), and Monitoring and Control (MAC) on the Return on Assets (ROA) of DMBs. The Random Effect Regression results reveal distinct impacts of these components on bank performance. The coefficient for RAS is -0.441012, with a standard error of 0.994948, a t-statistic of -0.443251, and a probability value of 0.6593, indicating an insignificant and potentially negative effect on ROA. In contrast, the coefficient for LES is 0.047793, with a standard error of 0.022815, a t-statistic of 2.094806, and a probability value of 0.0344, showing a statistically significant positive impact on ROA. Similarly, the coefficient for MAC is 0.082441, with a standard error of 0.038630, a t-statistic of 2.134119, and a probability value of 0.0289, indicating that robust monitoring and control positively influence bank performance. The model's weighted R-squared value is 0.625076, suggesting that 62.51 percent of the variation in ROA is explained by the model, with an adjusted R-squared of 0.427152. The F-statistic of 4.480127 (p-value = 0.037410) confirms the overall significance of the model. The findings highlight the importance of enhancing legal services and monitoring controls within forensic accounting frameworks to improve the financial performance of DMBs, while also suggesting a need for a reassessment of current risk assessment practices.